Analisis Proses Stress Relieving Annealing Terhadap Sambungan Las Gas Metal Arc Welding (Gmaw) Material Baja SS 400 - Andri Rudiyanto; Ratna Dewi Anjani; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
SS 400 steel (Structural Steel) is a type of low carbon steel (mild steel) which is classified into low alloy steel because its alloy composition is less than 8% with a composition of carbon (C) of 0.17%, manganese (Mn) 1.4%, phosphorus (P). ) 0.045%, and sulfur (S) 0.045%. Usually this steel is applied to bridge construction, plates on ships, oil tanks, and others. Almost every construction involves welding elements, although not a few in the welding process often cause residual stresses. Based on this, it is necessary to have a heat treatment process (stress relieving annealing) to reduce the residual stress and make the steel less brittle. The purpose of this study was to determine the effect on steel before and after the stress relieving annealing process at a temperature of 550oC with a holding time of about 30 minutes on the value of hardness and microstructure with Gas Metal Arc Welding (GMAW) welding process. The results showed that the highest hardness value was found in the raw material area of ​​the Heat Affected Zone (HAZ) of 353.14 HV and the lowest hardness value was found in heat treated steel located in the weld metal area.